2011
DOI: 10.1007/s11325-011-0632-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of obstructive sleep apnea and hypertension in Vietnam veterans with PTSD

Abstract: OSA severity and presence of self-reported hypertension are associated with poor auditory verbal memory and executive function in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Our sleep apnea findings in older, male veterans are supported by previous studies including a prospective study in older women which found an association between sleep apnea and an increased risk of dementia [4] as well as a cross-sectional study in older Vietnam-era veterans which found that obstructive sleep apnea severity was associated with worse cognitive performance [12].…”
Section: Resultssupporting
confidence: 88%
“…Our sleep apnea findings in older, male veterans are supported by previous studies including a prospective study in older women which found an association between sleep apnea and an increased risk of dementia [4] as well as a cross-sectional study in older Vietnam-era veterans which found that obstructive sleep apnea severity was associated with worse cognitive performance [12].…”
Section: Resultssupporting
confidence: 88%
“…Kinoshita (83%) and Yesavage (69%) required participants to be male, aged ≥ 55 with a CAPS score ≥ 40, each of which acts as a selection bias towards increased OSA prevalence. 41,42 Two studies by Mysliwiec 26,43 examined postcombat PSG in military personnel, and the second of these 43 required a PTSD Checklist Military Version score ≥ 50, both of which act as selection biases. The van Liempt study also included male veterans with a CAPS score > 50.…”
Section: 2640-44mentioning
confidence: 99%
“…[24][25][26][39][40][41][42][43][44] The clinic-based studies reported a prevalence range of 0.7% to 83%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kinoshita et al (2012) conducted a study through a PTSD Sleep Apnea Clinic, recruiting 120 PTSD patients to evaluate cognitive function. Patients currently treated for sleep apnea (e.g., corrective surgery, PAP-T) were excluded.…”
mentioning
confidence: 99%